Does the type of business activity and the enterprise location affect a firm’s survival? Results of an analysis for natural persons conducting economic activity in the Łódzkie Voivodship - Mikulec, Artur; Misztal, Małgorzata (Czy rodzaj prowadzonej działalności i lokalizacja przedsiębiorstwa wpływają na czas jego trwania? Wyniki analizy dla osób fizycznych prowadzących działalność gospodarczą w województwie łódzkim, 2018)
The article presents the results of the duration analysis for 21,163 enterprises (natural persons conducting economic activity) established in the Łódzkie Voivodship in 2010 and observed until December 31, 2015. The Kaplan-Meier estimation of the survival function, the Cox proportionalhazards model and the recursive partitioning method (the CTree algorithm) are applied to achieve the goal of the conducted research i.e. to answer the following question: does the type of business activity and location of the enterprise affect its duration? Prediction error curves based on the bootstrap crossvalidation estimates of the prediction error are used to assess and compare predictions obtained from all three models. On the basis of the analysis results it can be assumed that the type of business activity makes firms more varied due to their duration compared to their location
Econometrics = Ekonometria, 2018, Vol. 22, No. 3, s. 23-40
Keywords: enterprises; duration analysis; Kaplan-Meier survival curve; Cox proportional-hazardsmodel; survival trees; przedsiębiorstwa; analiza trwania; krzywa przeżycia Kaplana-Meiera; model proporcjonalnego hazardu Coxa; drzewa przeżycia